Wörterbuch des Neuen Testaments zur Erklärung der christlichen Lehre Sechs Auflagen: 1772-1805. Bibliothek der Neologie. Kritische Ausgabe in zehn Bänden. Band IX - Teller, Wilhelm Abraham (Mohr Siebeck, 2022)
The Prussian senior consistorial counsellor Wilhelm Abraham Teller (1734-1804) became one of the leading Enlightenment theologians thanks to his »Dictionary of the New Testament.« In this work he differentiated between »the unchanging doctrine (Lehre) of the Gospel« and its temporary teaching method (Lehrart). In this way, he strove to make the insights of historical-critical biblical scholarship fruitful for the practice of Christianity on the basis of the New Testaments main concepts. He also provides suggestions for a contemporary update of Luthers translation.
PublicationDate: 20220630
Keywords: Neues Testament -- Bibelwissenschaft -- Wörterbuch -- Aufklärungstheologie -- Schriftauslegung -- Editionen, Textausgaben -- Kirchengeschichte